The concept of Al-I‘Tibar and the fall of the Umayyads: an explicatory appraisal and its contemporaneity in understanding the present travails of Muslims - Adegboyega, Adebiyi Jelili; Ahmed Ibrahim, Hassan (IDOSI, 2011)
This article uses the Quranic philosophy of history, al-I‘tibar, in understanding what’s, why’s and how’s, which brought about the fall of the Umayyads. Based on this and the fact that history may, as Jeffrey Bartholet observes, “feed on itself,” the factors that caused the downfall of the Umayyads were on the one hand, explicatorily evaluated. On the other, these factors were assimilated within the present milieu of Muslims with a view to seeing how history has fed on itself. This study concludes that, failure to make good use of the objects of the lessons of history has created a situation whereby same factors which caused the fall of the Umayyads have significantly fed on themselves to cause the decline of the Muslim ummah.